A Prospective Study to Evaluate the Efficacy of the Fluorouracil, Leucovorin, Oxaliplatin, and Docetaxel Chemotherapy Regimen in Patients with Locally Advanced and Metastatic Adenocarcinoma of Stomach - Srinivasalu, Vijay Kumar; Philip, Arun; Pillai, Ranjini; Jose, Wesley M.; Keechilat, Pavithran (Indian Journal of Medical and Paediatric Oncology, 2022)
Introduction In India, patients with gastric cancer present at an advanced stage, and there is no standard chemotherapy regimen. Al-Batran's fluorouracil, leucovorin, oxaliplatin, and docetaxel (FLOT) chemotherapy gave us a glimmer of hope.Objectives Hence, we intended to evaluate the efficacy of FLOT chemotherapy in locally advanced and metastatic adenocarcinoma of stomach.Materials and Methods In this single-center, prospective cohort, patients with locally advanced and metastatic gastric adenocarcinoma who required chemotherapy between March 2016 and November 2017 were included in the study. All patients received standard FLOT chemotherapy. The primary objective was to evaluate the safety and efficacy of FLOT chemotherapy in the Indian population. Overall survival (OS) and progression-free survival (PFS) were calculated through the plotted Kaplan–Meier curves.Results In our study, 28 patients received FLOT chemotherapy. Their mean age was 55 years (range, 28–70 years) with a male preponderance (89.3%). Twenty-five patients had metastatic disease (89.3%), and three had locally advanced disease (10.7%). The median number of cycles was 4.5 (range, 1–8), and 75% received at least four cycles (n = 21). The hematological toxicities exhibited were neutropenia (50%) and febrile neutropenia (35.7%). Sixteen (57.1%) patients needed dose modifications due to treatment-related adverse effects (AEs). AEs led to treatment discontinuation in seven (25%) patients after the first cycle. The overall response rate in the intent-to-treat population was 52.7%, with the best-obtained response being a partial response, median PFS of 5 months, and median OS of 13 months.Conclusion FLOT chemotherapy regimens induced excellent responses but with significantly increased toxicity, needing dose modifications, and hence, should be considered only in a young and fit patient.
Keywords: adenocarcinoma of the stomach; fluorouracil; leucovorin; oxaliplatin; docetaxel chemotherapy; locally advanced; metastatic